Framework for music as store atmospherics to induce buying : a study of Delhi mall customers - Verma, Pranay (2013)
Music is a hidden stimulus for retailers. Not much has been researched on Indian luxury stores. This paper attempts to study the composition of music on perception of buyers at luxury stores. A research on customer’s buying intention was done to study their perception of music in the luxury store formats. This study uses exploratory factor analysis to find the significant different factors which constitute music to be played so as to induce buying in a luxury store. The composition of music depends upon music attractiveness, age of the customer and a desire to listen to the music.